User Satisfaction Analysis of QPON Indonesia Using TAM-IPA: Analisis Kepuasan Pengguna Aplikasi QPON Indonesia Menggunakan TAM-IPA - Nabila, Aisyatun; Waluyo, Minto (Academia Open, 2026)
General Background: Rapid digital transformation and increasing internet penetration in Indonesia have accelerated the adoption of application-based promotional services, including online discount voucher platforms. Specific Background: QPON Indonesia provides digital vouchers for shopping, food, beverages, and entertainment; however, negative user reviews on Google Play Store and App Store indicate unresolved service quality issues and unmet user expectations. Knowledge Gap: Previous studies on QPON Indonesia were limited to sentiment classification of user reviews and did not comprehensively measure user satisfaction or identify service improvement priorities using user acceptance constructs. Aims: This study aims to analyze user satisfaction with QPON Indonesia using the Technology Acceptance Model (TAM) and Importance Performance Analysis (IPA) and to determine priority attributes for service improvement. Results: The study involved 216 respondents and confirmed that all questionnaire items were valid and reliable. The overall satisfaction conformity level reached 88.2%, indicating that application performance had not fully met user expectations. IPA mapping identified four priority attributes in Quadrant I, namely PU4, PEOU1, PEOU2, and ATU2, which represent highly important attributes with relatively low performance. Recommended improvements include AI-personalized recommendations, User-Centered Design implementation, authentication system refinement, and gamification optimization. Novelty: This study integrates TAM and IPA to evaluate user satisfaction and determine service improvement priorities for QPON Indonesia based on negative user review indications. Implications: The findings provide practical insight for improving digital voucher application services and support strategic decision-making for application maintenance and user satisfaction management. Highlights: Overall conformity level reached 88.2%, indicating unmet user expectations. Four critical service attributes were categorized as high-priority improvement areas. Personalized recommendations and authentication refinement were proposed for service optimization. Keywords: IPA, QPON Indonesia, Satisfaction, TAM